2021
DOI: 10.1049/hve2.12175
|View full text |Cite
|
Sign up to set email alerts
|

Influence of imidazole derivatives on the dielectric and energy storage performance of epoxy

Abstract: Imidazoles are widely used as curing agents and accelerators for fabricating crosslinked epoxy materials applied in electrical and electronic fields. However, the intrinsic chemical structure of imidazole derivatives would greatly influence the polymerisation process, and further change the electrical properties, which was not emphasised. To achieve an indepth understanding, commonly used imidazole only containing pyridine-type nitrogen and imidazole with both pyridine and pyrrole-type nitrogen were selected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…48,59 all-trans TTTT dipoles. The dielectric permittivity of P(VDF-TrFE) at 1 kHz is 18, larger than that of PVDF (6)(7)(8)(9)(10)(11)(12), and the dielectric loss is less than 0.1. 60 Although P(VDF-TrFE) has a high dielectric permittivity, its high residual polarization makes it difficult to be applied in the field of energy storage.…”
Section: Synthesis and Versatile Dielectric Polarization Properties O...mentioning
confidence: 92%
See 2 more Smart Citations
“…48,59 all-trans TTTT dipoles. The dielectric permittivity of P(VDF-TrFE) at 1 kHz is 18, larger than that of PVDF (6)(7)(8)(9)(10)(11)(12), and the dielectric loss is less than 0.1. 60 Although P(VDF-TrFE) has a high dielectric permittivity, its high residual polarization makes it difficult to be applied in the field of energy storage.…”
Section: Synthesis and Versatile Dielectric Polarization Properties O...mentioning
confidence: 92%
“…Compared with P(VDF-HFP)/BT nanocomposites, the P(VDF-HFP)/BT@PANI nanocomposite shows that dielectric properties are notably promoted. As an example, the dielectric constant of BT@PANI/ P(VDF-HFP) is 99.1 at 1 kHz, which is 6.2 times larger than that of 20 vol% BT (16.1) and 9.6 times higher than that of P(VDF-HFP) (10). Zhao et al reported that a conductive carbon shell was coated onto the BT nanoparticles by a hydrothermal method.…”
Section: Synthesis and Versatile Dielectric Polarization Properties O...mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, materials with low dielectric constants are expected to achieve faster and stable signal transmission in microelectronic devices. 24,25 To address these needs, numerous studies have focused on developing resins with desirable electrical properties and stability at high temperatures. 26 For example, resin properties can be improved by adding inorganic fillers.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve miniaturization and portability, the size of electronic devices continues to shrink, introducing new obstacles such as signal crosstalk, power consumption and time delays. Therefore, materials with low dielectric constants are expected to achieve faster and stable signal transmission in microelectronic devices 24,25 …”
Section: Introductionmentioning
confidence: 99%